Evolved gas analyses of sedimentary rocks and eolian sediment in Gale Crater, Mars: Results of the Curiosity rover's sample analysis at Mars instrument from Yellowknife Bay to the Namib Dune. Issue 12 (7th December 2017) - Sutter, B.; McAdam, A. C.; Mahaffy, P. R.; Ming, D. W.; Edgett, K. S.; Rampe, E. B.; Eigenbrode, J. L.; Franz, H. B.; Freissinet, C.; Grotzinger, J. P.; Steele, A.; House, C. H.; et al.
Abstract: The sample analysis at Mars instrument evolved gas analyzer (SAM‐EGA) has detected evolved water, H2, SO2, H2 S, NO, CO2, CO, O2, and HCl from two eolian sediments and nine sedimentary rocks from Gale Crater, Mars. These evolved gas detections indicate nitrates, organics, oxychlorine phase, and sulfates are widespread with phyllosilicates and carbonates occurring in select Gale Crater materials. Coevolved CO2 (160 ± 248–2373 ± 820 μgC(CO2) /g) and CO (11 ± 3–320 ± 130 μgC(CO) /g) suggest that organic C is present in Gale Crater materials. Five samples evolved CO2 at temperatures consistent with carbonate (0.32 ± 0.05–0.70 ± 0.1 wt % CO3 ). Evolved NO amounts to 0.002 ± 0.007–0.06 ± 0.03 wt % NO3 . Evolution of O2 suggests that oxychlorine phases (chlorate/perchlorate) (0.05 ± 0.025–1.05 ± 0.44 wt % ClO4 ) are present, while SO2 evolution indicates the presence of crystalline and/or poorly crystalline Fe and Mg sulfate and possibly sulfide. Evolved H2 O (0.9 ± 0.3–2.5 ± 1.6 wt % H2 O) is consistent with the presence of adsorbed water, hydrated salts, interlayer/structural water from phyllosilicates, and possible inclusion water in mineral/amorphous phases. Evolved H2 and H2 S suggest that reduced phases occur despite the presence of oxidized phases (nitrate, oxychlorine, sulfate, and carbonate). SAM results coupled with CheMin mineralogical and Alpha‐Particle X‐ray Spectrometer elemental analyses indicate that Gale Crater sedimentary rocks have experienced a complex authigenetic/diagenetic history involving fluids with varying pH, redox, and salt composition. The inferred geochemical conditions were favorable for microbial habitability and if life ever existed, there was likely sufficient organic C to support a small microbial population. Key Points: The SAM instrument has detected evolved water, H2, SO2, H2S, NO, CO2, CO, O2, and HCl from Gale Crater sediments and sedimentary rock SAM detections are consistent with the presence of nitrate, organic C, carbonate, phyllosilicates, perchlorate, chlorate, and sulfate Gale Crater materials have experienced a complex authigenetic/diagenetic history with fluids of varying pH, redox, and salt composition